Vaccination with DNA Encoding the Immunodominant LACK Parasite Antigen Confers Protective Immunity to Mice Infected with Leishmania major - Gurunathan, Sanjay (The Rockefeller University Press, 1997)

(untitled)
To determine whether DNA immunization could elicit protective immunity to Leishmania major in susceptible BALB/c mice, cDNA for the cloned Leishmania antigen LACK was inserted into a euykaryotic expression vector downstream to the cytomegalovirus promoter. Susceptible BALB/c mice were then vaccinated subcutaneously with LACK DNA and challenged with L. major promastigotes. We compared the protective efficacy of LACK DNA vaccination with that of recombinant LACK protein in the presence or absence of recombinant interleukin (rIL)-12 protein. Protection induced by LACK DNA was similar to that achieved by LACK protein and rIL-12, but superior to LACK protein without rIL-12. The immunity conferred by LACK DNA was durable insofar as mice challenged 5 wk after vaccination were still protected, and the infection was controlled for at least 20 wk after challenge. In addition, the ability of mice to control infection at sites distant to the site of vaccination suggests that systemic protection was achieved by LACK DNA vaccination. The control of disease progression and parasitic burden in mice vaccinated with LACK DNA was associated with enhancement of antigen-specific interferon-γ (IFN-γ) production. Moreover, both the enhancement of IFN-γ production and the protective immune response induced by LACK DNA vaccination was IL-12 dependent. Unexpectedly, depletion of CD8(+) T cells at the time of vaccination or infection also abolished the protective response induced by LACK DNA vaccination, suggesting a role for CD8(+) T cells in DNA vaccine induced protection to L. major. Thus, DNA immunization may offer an attractive alternative vaccination strategy against intracellular pathogens, as compared with conventional vaccination with antigens combined with adjuvants.